Diseño de un manual de control interno para el departamento administrativo de la empresa Cemor S.A. - León Cedeño, José Antonio (2021)
The purpose of this study is to design an internal control manual for the administrative department, which is focused on the banana company CEMOR S.A. that presents a problem in its management that has generated a poor execution of the functions of the areas. Once the phenomenon investigated is understood, a theoretical examination is carried out on the relevance of internal control manuals and how this tool contributes to the administration and productivity of companies. Subsequently, the methodology that is based on a type of descriptive ideology with a mixed approach is contemplated by focusing on defining and understanding the structure, and shortcomings of the areas of the organization, which allows to visualize through surveys that the management, purchasing departments , accounting and secretary present deficiencies in guidelines for their processes, therefore, the proposal is determined according to this information, which allows to conclude that said instrument should contain 3 parts based on mentioning the functions and responsibilities of the personnel, the flowchart of the processes to guide the execution of activities and control policies to achieve a better development of the entity........